Application of melatonin in peripheral nerve injury repair - LIN Lining, SUN Mouyuan, WANG Huiming (Editorial Office of Stomatology, 2024)
The increasing incidence of peripheral nerve injuries brought on by trauma or tumors is substantially interfering with people's lives due to the causal sensory and motor dysfunctions. Peripheral nerves have some self-repair ability after injury, but they are limited by the degree of injury and the body's condition. The postoperative recovery of nerve function in patients is not satisfactory, which is closely related to the local inflammatory microenvironment after injury. Melatonin, a compound naturally synthesized in the pineal gland, protects peripheral nervous system cells from oxidative inflammation after injury and regulates their behavior and fate.Therefore, it has good application prospect in nerve tissue engineering. In this paper, we review the synthesis, metabolic processes underlying melatonin, mechanism of action as well as the current status of its application in peripheral nerve regeneration as well as potential application for oral diseases. In this way, it further provides a new idea for the clinical treatment of peripheral nerve injury.